Prevalence of ethical dilemmas in Slovenian family practice: Pogostnost etičnih dilem med zdravniki družinske medicine v Sloveniji - Klemenc-Ketiš, Zalika; Kersnik, Janko (Acta Medico-Biotechnica, 2022)
Purpose: To determine the perceived prevalence of ethical dilemmas in family practice. Methods: Self-administered questionnaire sent to a random sample of 259 Slovenian family physicians. The main outcome measure was the percentage of doctors reporting the frequency of ethical dilemmas on a 5-point scale. Results: Ethical dilemmas were common (mean score ± standard deviation, 36.2±12.5, out of a maximum of 100). The most common dilemmas involved decision-making regarding use of limited resources (23.9%), patient attempts to abuse the health care service (20.4%) and interfacing with the rest of the health care system (20.4%). Dealing with patients suspected of being physically abused, sexually abused, or involved in other violent acts was the least common ethical dilemma (<0.1%), followed by issues involving breaking bad news (<0.1%) and special situations regarding adolescents (0.7%). Older physicians and those with more experience reported ethical dilemmas less commonly (32.3±11.9 vs. 40.1±11.9, P < 0.001; 32.4±11.8 vs. 39.5±12.2, P = 0.001, respectively). Specialists in family medicine and family medicine residents reported ethical dilemmas more commonly than general practitioners without specialist training (37.0±12.6 vs. 30.7±10.8, P = 0.05 and 39.5±12.5 vs. 30.7±10.8, P = 0.04, respectively). Conclusions: Ethical issues are common in Slovenian family practice and are most often reported by residents in specialist training. This supports the need to continue and even improve specialist training in recognizing and comprehending ethical dilemmas.